2019
DOI: 10.29252/jhehp.5.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Virulence Characteristics of Yersinia enterocolitica Isolated from Dairy Products in the Northeast of Iran

Abstract: Virulence Dairy products [2, 4-6]. Y. enterocolitica is classified into six biotypes of 1A, 1B, 2, 3, 4, and 5, while it also has more than 70 different serotypes [1,7]. Based on their pathogenicity, Y. enterocolitica biotypes are classified as non-pathogenic biotype 1A and pathogenic biotypes of 1B, 2, 3, 4, and 5 [2, 6, 8]. Virulence in Y. enterocolitica could be categorized into two important structures, one of which is inside the chromosome and the other is on the plasmid of the Yersinia virulence (pYV) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…Seven biotype1A were isolated from raw milk, Yoghurt (two for each); white cheese, Kareish cheese, Ice cream (one for each) and 12 biotype 1B were isolated from Kareish cheese, raw milk, white cheese, Ice cream with total numbers of 4,3,3,2, respectively but failed to be detected from yoghurt samples. Similar biotypes were isolated from milk and its products by Gamal-Eldin(2008); Bernardino-Varo et al(2013); Ali et al(2015) and Tavassoli et al (2019) The results of in-vitro sensitivity tests for isolated Y. enterocolitica (Table 4) revealed that, the isolated Y. enterocolitica were highly resistant for Penicillin G. (100.0%); then methicillin (89.5%); oxytetracycline (79.0%); amoxicillin; ampicillin and streptomycin (73.7% for each) and erythromycin (63.2%). Meanwhile, they were intermediate sensitive to doxycycline (63.2%).…”
Section: Discussionsupporting
confidence: 62%
“…Seven biotype1A were isolated from raw milk, Yoghurt (two for each); white cheese, Kareish cheese, Ice cream (one for each) and 12 biotype 1B were isolated from Kareish cheese, raw milk, white cheese, Ice cream with total numbers of 4,3,3,2, respectively but failed to be detected from yoghurt samples. Similar biotypes were isolated from milk and its products by Gamal-Eldin(2008); Bernardino-Varo et al(2013); Ali et al(2015) and Tavassoli et al (2019) The results of in-vitro sensitivity tests for isolated Y. enterocolitica (Table 4) revealed that, the isolated Y. enterocolitica were highly resistant for Penicillin G. (100.0%); then methicillin (89.5%); oxytetracycline (79.0%); amoxicillin; ampicillin and streptomycin (73.7% for each) and erythromycin (63.2%). Meanwhile, they were intermediate sensitive to doxycycline (63.2%).…”
Section: Discussionsupporting
confidence: 62%
“…Biotype 1A is often considered to be non-pathogenic due to the absence of pYV plasmids (Bancerz-Kisiel, Pieczywek, Łada, & Szweda, 2018; Milad Tavassoli et al, 2019), while some studies reported that this biotype may produce symptoms similar to pathogenic biotypes (Bancerz-Kisiel et al, 2018;Tennant et al, 2003). Most of the strains that were isolated in the present study belonged to biotype 1A.…”
Section: Biotype Of Y Enterocoliticamentioning
confidence: 55%
“…Yersinia enterocolitica is involved in different human disorders such as gastro-enteritis, sepsis, appendicitis, and lymphadenitis ( Ahmed et al ., 2023 ). Yersiniosis as a gastrointestinal contagion comes afterward campylobacteriosis and salmonellosis ( Zadernowska et al , 2014 ) demonstrated by lymphadenitis, diarrhoea, appendicitis, and arthritis ( Tavassoli et al , 2019 ). Yersinia enterocolitica resists numerous antibacterial agents and is considered one of the pathogenic drug-resistant bacteria with a public health importance ( Sadek et al , 2014 ; Bonardi et al , 2018 ).…”
Section: Introductionmentioning
confidence: 99%